Effect of Cavity Configuration (C Factor) on the Marginal Adaptation of Low-Shrinking Composite: A Comparative Ex Vivo Study - Motaz A. Ghulman (International Journal of Dentistry)
Aim. To investigate the effect of C factor on marginal adaptation of low-shrinking composite (Silorane).The null hypothesis was that the marginal adaptation of “Silorane” is not affected by the cavity configuration. Materials and Methods. A Silorane based and a methacrylate based composites, with their corresponding self-etch adhesive systems “Filtek Silorane/Silorane Adhesive Bond System and Filtek Z250/Prompt L-Pop’’ respectively were used. Standardized cavities were prepared on the buccal surfaces of 100 maxillary premolars. Teeth were grouped into 5 groups (𝑛=20), for the 5 C factors. Restored teeth were subjected to thermocycling. Microleakage testing was done and linear dye penetration was assessed using a stereomicroscope. Statistical analysis was done using the Student’s t-test. Results. For the methacrylate based systems’ overall leakage score was significantly higher than the Silorane-based one (𝑃=0.034). For the methacrylate-based, leakage was found in all tested teeth groups except group 1 (C factor 1/5). For the Silorane, One-way ANOVA revealed a statistically significant increase in dye penetration in the 5th group (𝑃=0.010). Conclusions. The null hypothesis was rejected. The Silorane-based resin although it resulted in a statistically significant good marginal adaptation, it showed tendency toward a high leakage score with C-factor of 5.